2021
DOI: 10.1017/aap.2021.26
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Geochemical Sourcing of Granite Ground Stone

Abstract: Often understudied by archaeologists, ground stone tools (GST) were ubiquitous in the ancient Maya world. Their applications ranged from household tools to ceremonial equipment and beyond. Little attention has been focused on chemically sourcing the raw stone material used in GST production, largely because these tools were fashioned out of igneous or sedimentary rock, which can present characterization challenges. And, although portable X-ray fluorescence (pXRF) has been applied widely to source obsidian, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Few sources are mentioned in the literature, mainly at Tobago (Mones, 2007) and Puerto Rico (Turner et al, 2003), but other samples from La Désirade, Saint-Martin, British Virgin Islands, and French Guyana will be also integrated as references. Despite its granular texture, which induces a certain analytical challenges, petrographic observations coupled with geochemical analyses using X-ray fluorescence and X-ray spectroscopy in a SEM have been successfully employed in recent studies (e.g., Burg et al, 2021;Turbay et al, 2019). Sourcing of turquoise by non-destructive isotopic analysis Turquoise, another rock used for lapidary production during the Early and Middle Ceramic periods, is also studied in this project.…”
Section: Resultsmentioning
confidence: 99%
“…Few sources are mentioned in the literature, mainly at Tobago (Mones, 2007) and Puerto Rico (Turner et al, 2003), but other samples from La Désirade, Saint-Martin, British Virgin Islands, and French Guyana will be also integrated as references. Despite its granular texture, which induces a certain analytical challenges, petrographic observations coupled with geochemical analyses using X-ray fluorescence and X-ray spectroscopy in a SEM have been successfully employed in recent studies (e.g., Burg et al, 2021;Turbay et al, 2019). Sourcing of turquoise by non-destructive isotopic analysis Turquoise, another rock used for lapidary production during the Early and Middle Ceramic periods, is also studied in this project.…”
Section: Resultsmentioning
confidence: 99%
“…Ubiquitous during the Maya period, ground stone implements (including the mano and metate set) have received less theoretical and analytical attention than flaked stone lithics, perhaps because of the relegation of these artifacts to domestic, female-oriented activities. Recent studies have probed more deeply into their production and use (Brouwer Burg et al 2021;Duffy 2016;Searcy 2011). LeCount and colleagues (2022) examined the intensity of ground stone tool use across elite and commoner households and found that the latter peaked during the Late Classic, related to increased tax demands.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have developed methods for geochemically sourcing coarse grained, heterogenous rocks like granite using X-ray fluorescence (Brouwer Burg et al 2021;Tibbits et al 2022); this research reveals that ground stone tools were transported over long distances and has prompted new questions about exchange mechanisms. Geochemically based analysis of jadeite has also been fruitful (e.g., LA-ICP-MS, stable isotope analysis, elemental geochemistry; Kovacevich et al 2005), providing further data on trade and exchange.…”
Section: Discussionmentioning
confidence: 99%
“…Désirade, Saint-Martin, les îles Vierges britanniques et la Guyane française seront également intégrés en tant que références. Malgré sa texture granulaire, qui pose certaines difficultés analytiques, les observations pétrographiques couplées à des analyses géochimiques utilisant la fluorescence des rayons X et la spectroscopie des rayons X dans un MEB ont été employées avec succès dans des études récentes (e.g Burg et al, 2021;Turbay et al, 2019)…”
unclassified